Comparative study of two commercially pure titanium casting methods (Journal of Applied Oral Science, 2010)
The interest in using titanium to fabricate removable partial denture (RPD) frameworks has increased, but there are few studies evaluating the effects of casting methods on clasp behavior. OBJECTIVE: This study compared the occurrence of porosities and the retentive force of commercially pure titanium (CP Ti) and cobalt-chromium (Co-Cr) removable partial denture circumferential clasps cast by induction/centrifugation and plasma/vacuum-pressure. MATERIAL AND METHODS: 72 frameworks were cast from CP Ti (n=36) and Co-Cr alloy (n=36; control group). For each material, 18 frameworks were casted by electromagnetic induction and injected by centrifugation, whereas the other 18 were casted by plasma and injected by vacuum-pressure. For each casting method, three subgroups (n=6) were formed: 0.25 mm, 0.50 mm, and 0.75 mm undercuts. The specimens were radiographed and subjected to an insertion/removal test simulating 5 years of framework use. Data were analyzed by ANOVA and Tukey's to compare materials and cast methods (α=0.05). RESULTS: Three of 18 specimens of the induction/centrifugation group and 9 of 18 specimens of plasma/vacuum-pressure cast presented porosities, but only 1 and 7 specimens, respectively, were rejected for simulation test. For Co-Cr alloy, no defects were found. Comparing the casting methods, statistically significant differences (p